2023
DOI: 10.3390/w15152776
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Energy Loss Mechanism of Pump-Turbines with Splitter Blades under Different Characteristic Heads

Zhonghua Gui,
Zhe Xu,
Dongkuo Li
et al.

Abstract: The operating efficiency of high-head pump turbines is closely related to the internal hydraulic losses within the system. Conventional methods for calculating hydraulic losses based on pressure differences often lack detailed information on their distribution and specific sources. Additionally, the presence of splitter blades further complicates the hydraulic loss characteristics, necessitating further study. In this study, Reynolds-averaged Navier–Stokes (RANS) simulations were employed to analyze the perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The convergence criterion was set to 10 −5 . The residual value reached 10 −5 ; it was considered as convergence [28,29].…”
Section: Boundary Conditions and Calculation Methodsmentioning
confidence: 99%
“…The convergence criterion was set to 10 −5 . The residual value reached 10 −5 ; it was considered as convergence [28,29].…”
Section: Boundary Conditions and Calculation Methodsmentioning
confidence: 99%
“…Finally, they used the entropy generation theory to analyze the source of the loss, and pointed out that the hydraulic loss in the flow channel was mainly affected by the velocity gradient, not by the vortex structure. Many scholars [25][26][27] have studied the S-characteristic region through numerical calculations or PIV tests, obtained the flow and pressure-pulsation conditions at different working points, analyzed the positions of and reasons for vortex generation, and found that the flow under pump-braking conditions was the most unstable.…”
Section: Introductionmentioning
confidence: 99%